High-temperature-resistant aramid fiber coated lithium ion battery diaphragm and preparation process thereof

By using aramid composite slurry to enhance the coating layer of the lithium-ion battery separator, the existing separator is easily explosive and insufficient tensile strength when overheating is solved, and a separator with high tensile strength and high temperature resistance is achieved, improving the safety and performance of the battery.

CN119651043AActive Publication Date: 2025-03-18TAIZHOU JICUI FENGFANG NEW MATERIAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411860962.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-18
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

Existing lithium-ion battery separators are prone to shrinkage when overheating, and their safety is poor; although the non-woven separators are resistant to high temperatures, their tensile strength is low, making it difficult to meet the needs of high-end products.

Method used

The base film is reinforced by aramid composite slurry, and the coating layer is composed of aromatic polyester, adhesive, nanolignin, etc., and is prepared by water vapor preheating and hot air drying processes to form a separator with high tensile strength.

Benefits of technology

It improves the tensile strength and high temperature resistance of the diaphragm, enhances the safety and performance of the battery, and meets the needs of high-end products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005193190800000071
    Figure BDA0005193190800000071
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion battery components, and particularly discloses a high-temperature-resistant aramid fiber coated lithium ion battery diaphragm and a preparation process thereof. Aramid composite slurry is used for enhancing a base membrane, a liquid crystal phase is locally formed through 3, 5-dimethoxyphenyl, a xanthene structural unit is introduced, nano lignin is added as an auxiliary agent, and the xanthene structural unit and the nano lignin both contain a large number of aromatic ring structures, so that the liquid crystal phase is partially formed; the mechanical strength of the coating can be synergistically enhanced by virtue of a pi-pi stacking effect between aromatic rings and a liquid crystal phase, so that the defect of low tensile strength of a non-woven fabric diaphragm is overcome, and the requirements of high-end products can be fully met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium-ion battery components, and more specifically, to a high-temperature resistant aramid-coated lithium-ion battery separator and a preparation process thereof. Background Art

[0002] Lithium-ion battery is a secondary battery (rechargeable battery) that mainly relies on the movement of lithium ions between the positive electrode and the negative electrode to work. During the charge and discharge process, Li+ is embedded and de-embedded between the two electrodes: when charging, Li+ is de-embedded from the positive electrode and embedded into the negative electrode through the electrolyte, and the negative electrode is in a lithium-rich state; when discharging, the opposite is true. Lithium-ion batteries have the advantages of high energy density, high operating voltage, and long cycle life. They are very suitable for use in various mobile devices and electric vehicles, and have broad market prospects.

[0003] A diaphragm is usually arranged between the positive and negative electrodes of lithium-ion batteries. The diaphragm is a thin film material with a microporous structure located between the positive and negative electrodes. It ensures the normal transmission of lithium ions and electronic insulation while isolating the direct contact between the positive and negative electrodes. Although it does not directly participate in the electrochemical process, the pore structure and surface characteristics of the diaphragm have a direct impact on the internal resistance, discharge capacity, cycle stability and safety performance of the battery. Therefore, the diaphragm is also called the "third electrode" in the battery. Although the diaphragm does not participate in the electrochemical reaction, its structure, properties and surface chemistry are dynamically affected by the mechanical, thermal and electrochemical effects of the battery, further affecting ion transmission and battery safety. For example, the interaction between polyolefin diaphragms and electrolytes causes them to soften and expand mechanically, and the volume expansion of active materials during the cycle process will cause stress on the diaphragm. Therefore, in order to avoid the volume expansion of positive and negative electrode materials (such as lithium dendrite growth) during charging and discharging, causing battery short circuits, the diaphragm should have good tensile and puncture resistance. At present, the diaphragms on the market usually use olefin polymers as substrates, such as polyethylene diaphragms, polypropylene diaphragms, non-woven diaphragms, etc.

[0004] Regarding the above-mentioned related technologies, the inventor believes that the polyolefin separators in the related technologies are prone to shrinkage when the battery is overheated, which can cause the battery to explode and have poor safety. Although the non-woven fabric separator has good high temperature resistance, it has more structural voids and lower tensile strength, which makes it difficult to fully meet the needs of high-end products. Summary of the invention

[0005] In the related art, polyolefin separators have poor safety, while non-woven separators have low tensile strength, which makes it difficult to fully meet the needs of high-end products. In order to improve the above defects, the present application provides a high temperature resistant aramid coated lithium ion battery separator and a preparation process thereof.

[0006] In the first aspect, the present application provides a high temperature resistant aramid coated lithium ion battery separator, which adopts the following technical solution: A high-temperature resistant aramid coated lithium-ion battery separator comprises a base film and a coating coated on the surface of the base film, wherein the coating is obtained by coating an aramid composite slurry, preheating with water vapor, and drying with hot air, wherein the aramid composite slurry comprises the following components by weight percentage: 15-20% aromatic polyester, 5-8% adhesive, and the remainder being auxiliary agents and solvents; the aromatic polyester further contains xanthene structural units and 3,5-dimethoxyphenyl, and the auxiliary agent comprises nano-lignin, and the weight of the nano-lignin accounts for 0.8-1.4% of the total weight of the aramid composite slurry.

[0007] By adopting the above technical solution, the present application uses aramid composite slurry to strengthen the base film, and limits the aromatic polyester to contain 3,5-dimethoxyphenyl. 3,5-dimethoxyphenyl can make the molecules of aromatic polyester attract each other and orient regularly, thereby forming a liquid crystal phase locally, which provides a good basis for improving the mechanical properties of the diaphragm. The present application also limits the aromatic polyester to contain xanthene structural units, and adds nano-lignin as an auxiliary agent. Both the xanthene structural units and nano-lignin contain a large number of aromatic ring structures, which can increase the distribution density of aromatic rings in the coating, and have good compatibility with polyarylate. With the help of the π-π stacking effect between aromatic rings, a close attraction can be formed between aromatic polyester and nano-lignin. This attraction can synergistically enhance the mechanical strength of the coating with the liquid crystal phase, thereby making up for the defect of low tensile strength of non-woven membranes, and can fully meet the needs of high-end products.

[0008] Preferably, the aromatic polyester is prepared according to the following method: (1) mixing (3,5-dimethoxyphenyl)oxy-isophthalic acid, hydroquinone and xanthene monomers, adding a catalyst, and heating and polymerizing to obtain a prepolymer; in this step, the xanthene monomers include at least one of xanthene diphenol monomers and xanthene diacid monomers; (2) The prepolymer is subjected to a heat treatment to obtain an aromatic polyester.

[0009] By adopting the above technical scheme, the present application uses (3,5-dimethoxyphenyl)oxy-isophthalic acid, hydroquinone and xanthene monomers for co-condensation, introduces 3,5-dimethoxyphenyl through (3,5-dimethoxyphenyl)oxy-isophthalic acid, and introduces xanthene units through xanthene monomers, and finally obtains an aromatic polyester with liquid crystal effect and containing xanthene units.

[0010] Preferably, the xanthene monomer includes 9,9-bis(4-hydroxyphenyl)xanthene.

[0011] By adopting the above technical solution, 9,9-di(4-hydroxyphenyl)xanthene is a xanthene diphenol monomer that can react with (3,5-dimethoxyphenyl)oxy-isophthalic acid, and can improve the overall tensile strength of the diaphragm by introducing xanthene structural units.

[0012] Preferably, the 9,9-bis(4-hydroxyphenyl)xanthene is prepared according to the following method: Xanthone, thionyl chloride and DMF are mixed and heated to reflux, excess thionyl chloride is evaporated, and then the reaction system is cooled, and a xylene solution of phenol is added, and the mixture is heated to reflux again and then distilled under reduced pressure to evaporate xylene and excess phenol to obtain a crude product; the crude product is recrystallized using toluene to obtain 9,9-bis(4-hydroxyphenyl)xanthene.

[0013] By adopting the above technical scheme, the present application uses xanthone as a starting material, first treats the xanthone with thionyl chloride, replaces the carbonyl group with dichloromethylene, and then reacts the dichloromethylene with phenol, removes the chlorine atom and connects the phenol to the xanthene structure, thereby obtaining 9,9-di(4-hydroxyphenyl)xanthene that can undergo a co-condensation reaction with (3,5-dimethoxyphenyl)oxy-isophthalic acid.

[0014] Preferably, the xanthene monomer further includes 9,9-bis(4-carboxyphenoxyphenyl)xanthene.

[0015] By adopting the above technical solution, the present application further defines that the xanthene monomer includes 9,9-bis(4-carboxyphenoxyphenyl)xanthene, which is a xanthene diacid monomer. 9,9-bis(4-carboxyphenoxyphenyl)xanthene has two carboxyl groups and can be co-condensed with 9,9-bis(4-hydroxyphenyl)xanthene or hydroquinone, and can also improve the overall tensile strength of the diaphragm by introducing the xanthene structural unit.

[0016] Preferably, the 9,9-bis(4-carboxyphenoxyphenyl)xanthene is prepared according to the following method: 9,9-bis(4-cyanophenoxyphenyl)xanthene, potassium hydroxide and ethanol aqueous solution are mixed, heated under reflux and insoluble matter is filtered out to obtain a clear liquid, the clear liquid is cooled and then placed in an ice bath, hydrochloric acid is added for acidification to obtain a precipitate, the precipitate is washed, filtered and dried, and then recrystallized from anhydrous ethanol, and the product is dried under vacuum to obtain 9,9-bis(4-carboxyphenoxyphenyl)xanthene.

[0017] By adopting the above technical solution, the present application realizes the preparation of 9,9-di(4-carboxyphenoxyphenyl)xanthene.

[0018] Preferably, the auxiliary agent further comprises copolymer-modified halloysite nanotubes, wherein the copolymer-modified halloysite nanotubes are halloysite nanotubes with acrylic copolymer grafted on the surface, wherein the acrylic copolymer contains phenyl groups.

[0019] By adopting the above-mentioned technical scheme, the present application preferably uses copolymer-modified halloysite nanotubes as auxiliary agents. The copolymer-modified halloysite nanotubes can be entangled with the aromatic polyester through the long chains formed by the acrylic copolymer on the surface, and the phenyl groups in the acrylic copolymer can also improve the entanglement effect through the π-π stacking effect, so that the coating is not easy to break when stretched, thereby improving the overall tensile strength of the diaphragm.

[0020] Preferably, the copolymer-modified halloysite nanotubes are prepared according to the following method: (1) mixing halloysite nanotubes, vinyl triethoxysilane, water and ethanol, performing ultrasonic dispersion and then heating, and then filtering and washing to obtain vinyl-modified halloysite nanotubes; (2) Glycidyl methacrylate, ethyl 3-phenylacrylate, vinyl-modified halloysite nanotubes, an inhibitor and an anionic surfactant are added to deionized water, and a raw material solution is obtained after ultrasonic dispersion. An initiator is added to the raw material solution, and the raw material solution is filtered after heating reaction. The filter residue is crushed, and the copolymer-modified halloysite nanotubes are obtained after Soxhlet extraction and vacuum drying.

[0021] By adopting the above technical solution, the present application first uses vinyl triethoxysilane to graft a silane segment with a vinyl group on the surface of the halloysite nanotube, and then copolymerizes the vinyl group at the end of the silane segment with two monomers, glycidyl methacrylate and ethyl 3-phenylacrylate, under the action of an initiator, thereby forming a long chain of acrylic copolymer with a phenyl group on the surface of the halloysite nanotube, and obtaining a copolymer-modified halloysite nanotube. Glycidyl methacrylate gives the polymer good flexibility and adhesion, which helps to fully improve the tensile strength of the entire diaphragm.

[0022] Preferably, in the step (2) of preparing the copolymer-modified halloysite nanotubes, the raw materials for preparing the raw material solution further include linolenic acid.

[0023] By adopting the above technical solution, the linolenic acid molecule has three unsaturated bonds, which can participate in the copolymerization of acrylic acid monomers and produce more branched structures in the copolymer, thereby promoting full contact between the acrylic copolymer chain segments and the aromatic polyester, and helping to fully improve the overall tensile strength of the diaphragm.

[0024] In a second aspect, the present application provides a preparation process of a high temperature resistant aramid coated lithium ion battery separator, which adopts the following technical solution.

[0025] A preparation process of a high temperature resistant aramid coated lithium ion battery separator, comprising the following steps: (1) mixing aromatic polyester, adhesive, additive and solvent, stirring to obtain aramid composite slurry, and setting aside; performing corona pretreatment on lithium ion battery base film, and setting aside; (2) coating the aramid composite slurry on the surface of the lithium-ion battery base film to obtain a coating layer; (3) The coating layer is preheated and then dried with hot air to obtain a high temperature resistant aramid coated lithium ion battery separator.

[0026] By adopting the above-mentioned technical scheme, the present application first prepares the aramid composite slurry and pretreats the base film, then solidifies the aramid composite slurry through coating, preheating, drying and other steps, and forms pores through the evaporation of the solvent, thereby obtaining a high-temperature resistant aramid coated lithium-ion battery separator suitable for use in lithium battery products.

[0027] In summary, this application has the following beneficial effects: 1. This application uses aramid composite slurry to reinforce the base film, forms a liquid crystal phase locally through 3,5-dimethoxyphenyl, introduces xanthene structural units, and adds nano-lignin as an auxiliary agent. Both the xanthene structural units and nano-lignin contain a large number of aromatic ring structures, which can synergistically enhance the mechanical strength of the coating through the π-π stacking effect between the aromatic rings and the liquid crystal phase, thereby compensating for the defect of low tensile strength of the non-woven fabric diaphragm and fully meeting the needs of high-end products.

[0028] 2. The present application selects 9,9-bis(4-hydroxyphenyl)xanthene and 9,9-bis(4-carboxyphenoxyphenyl)xanthene as xanthene monomers. The xanthene structural unit is introduced through these two monomers, which increases the distribution density of aromatic rings in the coating and helps to improve the overall tensile strength of the diaphragm.

[0029] 3. The present application also uses copolymer-modified halloysite nanotubes as an auxiliary agent. The copolymer-modified halloysite nanotubes can be entangled with the aromatic polyester through the long chains formed by the acrylic copolymer on the surface, and the phenyl groups in the acrylic copolymer can also improve the entanglement effect through the π-π stacking effect, so that the coating is not easy to break when stretched, thereby improving the overall tensile strength of the diaphragm. DETAILED DESCRIPTION

[0030] The present application is further described in detail below in conjunction with embodiments, preparation examples and comparative examples. The raw materials involved in the present application can all be obtained commercially.

[0031] Preparation Example of Aromatic Polyester The following is an explanation using Preparation Example 1.

[0032] Preparation Example 1 In this preparation example, the xanthene monomer is 9,9-bis(4-hydroxyphenyl)xanthene, and 9,9-bis(4-hydroxyphenyl)xanthene is prepared according to the following method: Weigh xanthone, thionyl chloride, DMF, phenol and xylene in a ratio of 30 g:100 mL:0.2 mL:50 g:100 mL and set aside; mix xanthone, thionyl chloride and DMF and heat to reflux for 8 h, evaporate excess thionyl chloride, then cool the reaction system to 25°C, add a xylene solution of phenol, heat to reflux for 10 h again, and then perform reduced pressure distillation to evaporate xylene and excess phenol to obtain a crude product; recrystallize the crude product using toluene to obtain 9,9-di(4-hydroxyphenyl)xanthene.

[0033] This preparation example provides an aromatic polyester, which is prepared according to the following method: (1) 1 mol of (3,5-dimethoxyphenyl)oxy-isophthalic acid, 1 mol of hydroquinone and 0.5 mol of 9,9-di(4-hydroxyphenyl)xanthene were mixed, 0.1 mol of tetrabutyl titanate was added as a catalyst, and the mixture was heated and polymerized at 195° C. under normal pressure for 12 hours to obtain a prepolymer; (2) The prepolymer was heated at 225° C. and 0.05 MPa for 16 h to obtain an aromatic polyester.

[0034] Preparation Example 2 The difference between this preparation example and preparation example 1 is that the xanthene monomer also includes 9,9-di(4-carboxyphenoxyphenyl)xanthene, and in the step (1) of preparing the aromatic polyester, 0.8 mol of (3,5-dimethoxyphenyl)oxy-isophthalic acid, 0.2 mol of 9,9-di(4-carboxyphenoxyphenyl)xanthene, 1 mol of hydroquinone and 0.5 mol of 9,9-di(4-hydroxyphenyl)xanthene are mixed.

[0035] 9,9-bis(4-carboxyphenoxyphenyl)xanthene was prepared as follows: 9,9-bis(4-cyanophenoxyphenyl)xanthene, potassium hydroxide and ethanol aqueous solution (the volume ratio of ethanol to water is 1:1) are weighed in a ratio of 0.045 mol:0.45 mol:300 mL, 9,9-bis(4-cyanophenoxyphenyl)xanthene, potassium hydroxide and ethanol aqueous solution are mixed, and insoluble matter is filtered out after heating and refluxing for 48 hours to obtain a clear liquid, and the clear liquid is cooled to 25° C. and placed in an ice bath, and hydrochloric acid is added to acidify to pH=2.5 to obtain a precipitate, and the precipitate is washed, filtered and dried, and then recrystallized from anhydrous ethanol, and the product is dried under vacuum to obtain 9,9-bis(4-carboxyphenoxyphenyl)xanthene.

[0036] Preparation example of copolymer modified halloysite nanotubes The following is an explanation using Preparation Example 3.

[0037] Preparation Example 3 This preparation example provides a copolymer-modified halloysite nanotube, which is prepared according to the following method: (1) mixing halloysite nanotubes (CAS No.: 60676-86-0), vinyl triethoxysilane, water and ethanol in a weight ratio of 1:0.1:20:10, and then heating at 110° C. for 8 h after ultrasonic dispersion for 1 h, followed by filtering and washing to obtain vinyl-modified halloysite nanotubes; (2) Glycidyl methacrylate, ethyl 3-phenylacrylate, vinyl-modified halloysite nanotubes, an inhibitor (copper sulfate pentahydrate), an anionic surfactant (sodium dodecylbenzene sulfonate) and deionized water are mixed in a weight ratio of 0.3:2.7:1:1:10, and a raw material solution is obtained after ultrasonic dispersion. An initiator (ammonium persulfate, with an amount of 0.5% of the total weight of the raw material solution) is added to the raw material solution, and the mixture is heated at 70° C. for reaction for 4 h and then filtered. The filter residue is crushed, and the copolymer-modified halloysite nanotubes is obtained after Soxhlet extraction and vacuum drying.

[0038] Preparation Example 4 The difference between this preparation example and preparation example 3 is that in step (2) of preparing copolymer-modified halloysite nanotubes, the raw materials for preparing the raw material solution also include linolenic acid, and the weight ratio of linolenic acid to vinyl-modified halloysite nanotubes is 1:10.

[0039] Preparation Example 5 This Preparation Example is different from Preparation Example 3 in that glycidyl methacrylate is replaced with the same weight of ethyl 3-phenylacrylate. Example

[0040] Examples 1-5 The following description is given by taking Example 1 as an example.

[0041] Example 1 In this embodiment, nano-lignin is used as an auxiliary agent, the average particle size of the nano-lignin is 320nm, and it is made of dealkalized lignin; the aromatic polyester is prepared according to the method of Preparation Example 1, the adhesive is vinylidene fluoride-trifluoroethylene copolymer, and the solvent is DMF.

[0042] The present embodiment provides a high-temperature resistant aramid-coated lithium-ion battery separator, comprising a base film and a coating coated on the surface of the base film, wherein the base film is a PET non-woven fabric with a thickness of 20 μm and a porosity of 62%, and the coating is obtained by coating an aramid composite slurry, preheating with water vapor, and drying with hot air, wherein the aramid composite slurry comprises the following components by weight percentage: 15% aromatic polyester, 8% adhesive, 0.8% nano-lignin, and the remainder being a solvent.

[0043] This embodiment provides a preparation process of a high temperature resistant aramid coated lithium ion battery separator, comprising the following steps: (1) mixing aromatic polyester, adhesive, additive and solvent, stirring to obtain aramid composite slurry, and setting aside; performing corona pretreatment on lithium ion battery base film, and setting aside; (2) coating the aramid composite slurry on both sides of the lithium-ion battery base film by gravure coating at a coating rate of 5 m / min to obtain a coating layer; (3) The coating layer was preheated with water vapor for 15 seconds in an environment with 95% humidity, and then dried with hot air to solidify the coating layer into a coating with a thickness of 5 μm, thereby obtaining a high-temperature resistant aramid coated lithium-ion battery separator.

[0044] As shown in Table 1, the main difference between Examples 1-5 is that the raw material ratios of the aramid composite slurry are different.

[0045] Table 1 Raw material ratio of aramid composite slurry Example 6 The difference between this embodiment and embodiment 5 is that the aromatic polyester is prepared according to the method of preparation example 2.

[0046] Example 7 The difference between this embodiment and embodiment 6 is that nano-lignin and copolymer-modified halloysite nanotubes are used together as auxiliary agents, the copolymer-modified halloysite nanotubes are prepared according to the method of preparation example 3, and the mass fractions of nano-lignin and copolymer-modified halloysite nanotubes in the aramid composite slurry are 1.4% and 2.5%, respectively.

[0047] Example 8 The difference between this embodiment and embodiment 7 is that the copolymer-modified halloysite nanotubes are prepared according to the method of preparation example 4.

[0048] Example 9 The difference between this embodiment and embodiment 7 is that the copolymer-modified halloysite nanotubes are prepared according to the method of preparation example 5.

[0049] Comparative Example Comparative Example 1 The difference between this comparative example and Example 1 is that the aromatic polyester in Preparation Example 1 is replaced by an aromatic polyester (LCP T820) provided by Mitsubishi Engineering-Plastics Corporation of Japan.

[0050] Comparative Example 2 The difference between this comparative example and Example 1 is that the xanthene monomer used in preparing the aromatic polyester is replaced by hydroquinone in an equal molar amount.

[0051] Comparative Example 3 The difference between this comparative example and Example 1 is that the (3,5-dimethoxyphenyl)oxy-isophthalic acid used in the preparation of the aromatic polyester is replaced by isophthalic acid in an equal molar amount.

[0052] Comparative Example 4 The difference between this comparative example and Example 1 is that the components of the aramid composite slurry do not include nano-lignin.

[0053] Performance testing methods The tensile strength of the diaphragm of each embodiment and comparative example was tested by a universal tensile machine (Zwick Z100). The sample size was 20 mm × 80 mm, and the tensile speed was 10 mm / min. After the test, the tensile strength of comparative example 1 was used as a benchmark to calculate the ratio between the tensile strength of each embodiment and comparative example and the tensile strength of comparative example 1. The ratio was recorded as the relative tensile strength. The results are shown in Table 2.

[0054] Table 2 Relative tensile strength sample Relative tensile strength / % Example 1 126.8 Example 2 127.4 Example 3 128.3 Example 4 128.7 Example 5 129.5 Example 6 134.8 Example 7 138.6 Example 8 140.2 Example 9 136.1 Comparative Example 1 100.0 Comparative Example 2 110.4 Comparative Example 3 106.8 Comparative Example 4 114.7 Combining Examples 1-5 and Comparative Example 1 and Table 2, it can be seen that the relative tensile strength measured in Examples 1-5 is higher than that in Comparative Example 1. This is because Comparative Example 1 lacks aromatic polyester containing xanthene structural units and 3,5-dimethoxyphenyl. In this case, it is difficult to fully improve the tensile strength of the separator by relying solely on nano-lignin. In Examples 1-5, 3,5-dimethoxyphenyl forms a liquid crystal phase locally, and the xanthene structural units and nano-lignin can enhance the mechanical strength of the coating in synergistic relationship with the liquid crystal phase by means of the π-π stacking effect between the aromatic rings, thereby making up for the defect of low tensile strength of the non-woven membrane, and thus being able to fully meet the needs of high-end products.

[0055] Combining Example 1 and Comparative Example 2 and Table 2, it can be seen that the relative tensile strength measured in Example 1 is higher than that in Comparative Example 2. This is because the aromatic polyester in Comparative Example 2 lacks xanthene structural units, which makes it impossible to fully exert the π-π stacking effect between the aromatic rings, resulting in the synergistic effect between the π-π stacking effect and the liquid crystal phase being affected. Therefore, the tensile strength measured in Comparative Example 2 is lower.

[0056] Combining Example 1 and Comparative Example 3 and Table 2, it can be seen that the relative tensile strength measured in Example 1 is higher than that in Comparative Example 3. This is because the aromatic polyester in Comparative Example 3 lacks 3,5-dimethoxyphenyl and cannot improve the tensile strength by forming a liquid crystal phase. At the same time, it also destroys the synergistic effect between the π-π stacking effect and the liquid crystal phase. Therefore, the tensile strength of Comparative Example 3 is lower.

[0057] Combining Example 1 and Comparative Example 4 and Table 2, it can be seen that the relative tensile strength measured in Example 1 is higher than that in Comparative Example 4. This is because Comparative Example 4 lacks nano-lignin, which affects the synergistic effect between the π-π stacking effect and the liquid crystal phase, so the tensile strength of Comparative Example 4 is lower.

[0058] Combining Example 5 and Example 6 and Table 2, it can be seen that the relative tensile strength measured in Example 6 is higher. This is because the aromatic polyester in Example 6 contains 9,9-di(4-carboxyphenoxyphenyl)xanthene structural units, and the density of aromatic rings is higher. Therefore, the synergistic effect between the π-π stacking effect and the liquid crystal phase is stronger, so that the tensile strength is improved.

[0059] Combining Example 6 and Example 7 with Table 2, it can be seen that the relative tensile strength measured in Example 7 is higher. This is because the copolymer-modified halloysite nanotubes can be entangled with the aromatic polyester through the long chains formed by the acrylic copolymer on the surface, and the phenyl groups in the acrylic copolymer can also improve the entanglement effect through the π-π stacking effect, so that the coating is not easy to break when pulled, thereby improving the overall tensile strength of the diaphragm.

[0060] Combining Example 7 and Example 8 with Table 2, it can be seen that the relative tensile strength measured in Example 8 is higher. This is because the linolenic acid molecule has three unsaturated bonds, which can participate in the copolymerization of acrylic acid monomers and produce more branched structures in the copolymer, thereby promoting full contact between the acrylic copolymer chain segments and the aromatic polyester, strengthening the bonding between the molecular chains, and helping to fully improve the overall tensile strength of the diaphragm.

[0061] Combining Example 7 and Example 9 with Table 2, it can be seen that the relative tensile strength measured in Example 7 is relatively high, because the glycidyl methacrylate in Example 7 gives the polymer good flexibility and adhesion, which helps to fully improve the tensile strength of the entire diaphragm. However, the copolymer on the surface of the copolymer-modified halloysite nanotubes in Example 9 lacks the glycidyl methacrylate structural unit, so the tensile strength of Example 9 is relatively low.

[0062] The above embodiments are merely explanations of the present application and are not limitations of the present application. After reading this specification, those skilled in the art may make modifications to the embodiments of the present application without any creative contribution as needed. However, as long as they are within the scope of the claims of the present application, they are protected by the patent law.

Claims

1. A high temperature resistant aramid coated lithium ion battery separator, characterized in that: The invention comprises a base film and a coating coated on the surface of the base film, wherein the coating is obtained by coating an aramid composite slurry, preheating with water vapor and drying with hot air, and the aramid composite slurry comprises the following components by weight percentage: 15-20% aromatic polyester, 5-8% adhesive, and the remainder being auxiliary agents and solvents; the aromatic polyester also contains xanthene structural units and 3,5-dimethoxyphenyl, and the auxiliary agent comprises nano-lignin, and the weight of the nano-lignin accounts for 0.8-1.4% of the total weight of the aramid composite slurry.

2. The high temperature resistant aramid coated lithium ion battery separator according to claim 1, characterized in that: The aromatic polyester is prepared according to the following method: (1) mixing (3,5-dimethoxyphenyl)oxy-isophthalic acid, hydroquinone and xanthene monomers, adding a catalyst, and heating and polymerizing to obtain a prepolymer; in this step, the xanthene monomers include at least one of xanthene diphenol monomers and xanthene diacid monomers; (2) The prepolymer is subjected to a heat treatment to obtain an aromatic polyester.

3. The high temperature resistant aramid coated lithium ion battery separator according to claim 2, characterized in that: The xanthene monomer includes 9,9-bis(4-hydroxyphenyl)xanthene.

4. The high temperature resistant aramid coated lithium ion battery separator according to claim 3, characterized in that: The 9,9-bis(4-hydroxyphenyl)xanthene is prepared according to the following method: Xanthone, thionyl chloride and DMF are mixed and heated to reflux, excess thionyl chloride is evaporated, and then the reaction system is cooled, and a xylene solution of phenol is added, and the mixture is heated to reflux again and then distilled under reduced pressure to evaporate xylene and excess phenol to obtain a crude product; the crude product is recrystallized using toluene to obtain 9,9-bis(4-hydroxyphenyl)xanthene.

5. The high temperature resistant aramid coated lithium ion battery separator according to claim 3, characterized in that: The xanthene monomers also include 9,9-bis(4-carboxyphenoxyphenyl)xanthene.

6. The high temperature resistant aramid coated lithium ion battery separator according to claim 5, characterized in that: The 9,9-bis(4-carboxyphenoxyphenyl)xanthene is prepared according to the following method: 9,9-bis(4-cyanophenoxyphenyl)xanthene, potassium hydroxide and ethanol aqueous solution are mixed, heated under reflux and insoluble matter is filtered out to obtain a clear liquid, the clear liquid is cooled and then placed in an ice bath, hydrochloric acid is added for acidification to obtain a precipitate, the precipitate is washed, filtered and dried, and then recrystallized from anhydrous ethanol, and the product is dried under vacuum to obtain 9,9-bis(4-carboxyphenoxyphenyl)xanthene.

7. The high temperature resistant aramid coated lithium ion battery separator according to claim 1, characterized in that: The auxiliary agent also includes copolymer-modified halloysite nanotubes. The copolymer-modified halloysite nanotubes are halloysite nanotubes with acrylic copolymers grafted on the surface. The acrylic copolymers contain phenyl groups.

8. The high temperature resistant aramid coated lithium ion battery separator according to claim 7, characterized in that: The copolymer modified halloysite nanotubes are prepared according to the following method: (1) mixing halloysite nanotubes, vinyl triethoxysilane, water and ethanol, performing ultrasonic dispersion and then heating, and then filtering and washing to obtain vinyl-modified halloysite nanotubes; (2) Glycidyl methacrylate, ethyl 3-phenylacrylate, vinyl-modified halloysite nanotubes, an inhibitor and an anionic surfactant are added to deionized water, and a raw material solution is obtained after ultrasonic dispersion. An initiator is added to the raw material solution, and the raw material solution is filtered after heating reaction. The filter residue is crushed, and the copolymer-modified halloysite nanotubes is obtained after Soxhlet extraction and vacuum drying.

9. The high temperature resistant aramid coated lithium ion battery separator according to claim 8, characterized in that: In the step (2) of preparing the copolymer-modified halloysite nanotubes, the raw materials for preparing the raw material solution also include linolenic acid.

10. The process for preparing the high temperature resistant aramid coated lithium ion battery separator according to any one of claims 1 to 9, characterized in that: The following steps are involved: (1) mixing aromatic polyester, adhesive, additive and solvent, stirring to obtain aramid composite slurry, and setting aside; performing corona pretreatment on lithium ion battery base film, and setting aside; (2) coating the aramid composite slurry on the surface of the lithium-ion battery base membrane to obtain a coating layer; (3) The coating layer is preheated and then hot-air dried to obtain a high-temperature resistant aramid-coated lithium-ion battery separator.

Citation Information

Patent Citations

  • Preparation of high-safety ceramic-coated separator and application of ceramic-coated separator in lithium ion battery

    CN107331825A

  • Polyaramide with xanthene structure and preparation method thereof

    CN108676159A

  • Xanthene-structured aromatic polyamide prepared based on xanthene diiodide compound and method of preparation

    CN109824889A